Sex-related differences in patients with acute aortic syndromes
INTRODUCTION: Heterogeneity in the epidemiology, management, and in-hospital outcomes of patients with acute aortic syndromes can be found among male and female populations. This study aims to analyze sex-related differences in a cohort of patients treated in a tertiary university center. METHODS: All patients admitted with acute aortic syndromes between January 2012 and January 2023 were retrospectively analyzed. A descriptive analysis of the data was performed, and the results were queried to explore sex-related differences according to the type of aortic syndrome, type of treatment (medical or surgical – conventional or endovascular), and the temporal phase of the disease in which this treatment occurred. A multivariable logistic regression was undertaken to identify variables associated with higher in-hospital mortality. Variables were included if statistically significant in the univariable analysis or if considered medically relevant. RESULTS: A total of 116 patients (69% male) were included. Women were older (median age [interquartile range]: 64.6 years [40–85 years], n=36 versus 58.7 [23–84], n=80; P=0.034), had a higher proportion of intramural hematoma (19.4% versus 5.0%, P=0.014) and a lower proportion of aortic dissection (72.2% versus 88.8%, P=0.026) compared to men. Both sexes were more frequently treated with medical therapy alone (33.6%). However, women had a trend towards a lower proportion of open surgical management compared to men (16.7% versus 23.8%, P=0.391), as well as higher in-hospital mortality associated with this type of treatment (50.0% versus 21.1%, P=0.169). Additionally, women were associated with a higher conversion to endovascular or open surgery when first managed conservatively (13.9% versus 3.8%, P=0.046). In binary logistic regression, age was associated with higher in-hospital mortality (OR 1.056 [95% CI, 1.01-1.10]; P=0.014), but not female sex (OR 1.133 [95% CI, 0.39-3.30]; P=0.819). CONCLUSION: Women were older, had more intramural hematoma, and were associated with a higher conversion from medical to surgical treatment. After multivariable regression, age was associated with higher in-hospital mortality, but female sex was not. Larger cohorts are needed to understand if intervention in female patients will have an impact on intra-hospital mortality.